Use of Reflective Teaching in Reading Comprehension Achievement among Students with Emotional Behavioral Disorder - Obiyo, Ngozi; Omeje, Matina; Ebimgbo, Samuel; Obikeguna, Christy (International Journal of Psychosocial Rehabilitation, 2024)
In this study, reflective teaching was used to improve the reading comprehension achievement ofstudents with emotional behavioral disorder in Nsukka Local Government Area of Enugu State, Nigeria.Particular attention was paid to the location of the schools as moderating factor. Three research questions andtwo null hypotheses guided the study. The population of the study was 152 Junior Secondary School II1 studentswith emotional behavioral disorder. A sample of 35 of the students from four co-educational schools was usedfor the study. Reading Comprehension Achievement test was used to collect data. The instrument was facevalidated by three experts, from University of Nigeria Nsukka. Content validation of the instrument was ensuredthrough the use of a test blueprint. A reliability index of 0.86 was obtained using Pearson’s product momentcorrelation. Data collected were analyzed using mean, standard deviation and analysis of covariance. Resultsshow that students exposed to reflective teaching achieved higher mean reading comprehension than theircounterparts in the control group. There was no significant interaction effect of method and location on readingcomprehension achievement of students with emotional behavioral disorder.